Evidence for a common biological pathway linking three Parkinson's disease‐causing genes: parkin, PINK1 and DJ‐1. (11th March 2015) - van der Merwe, Celia; Jalali Sefid Dashti, Zahra; Christoffels, Alan; Loos, Ben; Bardien, Soraya
Abstract Parkinson's disease (PD) is characterised by the loss of dopaminergic neurons in the midbrain. Autosomal recessive, early‐onset cases of PD are predominantly caused by mutations in the parkin, PINK1 and DJ‐1 genes. Animal and cellular models have verified a direct link between parkin and PINK1, whereby PINK1 phosphorylates and activates parkin at the outer mitochondrial membrane, resulting in removal of dysfunctional mitochondria via mitophagy. Despite the overwhelming evidence for this interaction, few studies have been able to identify a link for DJ‐1 with parkin or PINK1. The aim of this review is to summarise the functions of these three proteins, and to analyse the existing evidence for direct and indirect interactions between them. DJ‐1 is able to rescue the phenotype of PINK1‐knockout Drosophila models, but not of parkin‐knockouts, suggesting that DJ‐1 may act in a parallel pathway to that of the PINK1/parkin pathway. To further elucidate a commonality between these three proteins, bioinformatics analysis established that Miro (RHOT1) interacts with parkin and PINK1, and HSPA4 interacts with all three proteins. Furthermore, 30 transcription factors were found to be common amongst all three proteins, with many of them being involved in transcriptional regulation. Interestingly, expression of these proteins and their associated transcription factors are found to be significantly down‐regulated in PD patients compared to healthy controls. In summary, this review provides insight into common pathways linking three PD‐causing genes and highlights some key questions, the answers to which may provide critical insight into the disease process.